The Effect of Leader-Member Exchange on Organizational Citizenship Behavior Mediated by Job Satisfaction - Alwi, Saemu; Sri Wiyati Mahrani (International Journal of Management and Education in Human Development, 2021)
This study aimed to examine and analyze the effect of leader-member organizational citizenship behavior mediated by job satisfaction. This study uses a descriptive analysis with path analysis as an analytical tool. Sampling uses the census method, namely the total population used as research respondents, namely as many as 48 random sampling employees. The research instrument test used the validity test and the instrument reliability test. The analytical tool used in this research is the analysis of PLS-SEM results, which showed that the Leader-Member is positive but not significant. Leader-Member positive and significant effect on Job Satisfaction. Job satisfaction has a significant positive impact on OCB. Impacts a significant substantial mediated by Job Satisfaction.